Managing Budgetary Virements - Saxena, Sandeep (Technical Notes and Manuals; Technical Notes and Manuals ;, 2016)
Virements are useful instruments of budget flexibility. If carried out transparently and within accepted limits, virements can promote expenditure efficiency. Large, unregulated virements can undermine budget credibility and the budget's relevance as principal policy and financial planning instrument. This note defines virements, clarifies their purpose, and specifies what general and country-specific considerations should guide the design of a virement framework. The note argues that countries should design virement policies maintaining balance between their budget flexibility and accountability needs, and keeping in view the legal-cultural environment and the state of development of their public financial management.